Malay customary tenure and conflict on implementation of colonial land law in Peninsular Malaysia. - Hassan Zaki, Pakhriazad; Hamzah, Mohd Zaki; Ismail, Mohd Hasmadi; Awang, Khairil Wahidin; Abdul Hamid, Hazandy (Academic Journals, 2010)
Since the independence in 1957, land tenure system in the Peninsular Malaysia (PM) has changed. The land law and regulations have been frequently amended so that the provisions and rationale of the laws can be properly understood and continuously evaluated to suit the current requirements. This paper review the Malay customary land tenure and the development of colonial land system, which has be examined through its historical evident with the aid of law cases. Even though the modern system of land tenure and land law has been widely observed and has governed land dealings in the country, customary land tenure system are still much influenced and practiced especially among the rural Malay society. The Malay customary law consists of customs and traditions of the Malay, which in the course of time acquired the character of laws and can be only, enforced by the chief or elders. It must be ancient, certain and reasonable and being in derogation of the general rules of law, and construed strictly. The paper identified the mixtures and interaction of both systems, which has been developed by the colonials to displace the existing indigenous Malay customary land tenure. The development of modern land tenure system was explained in the context of the different separate entities other than historical study on the previous land law before the commencement of the current act. Therefore, by combining the ancient Malay customary tenure, the period of colonial and the post independence land tenure system, this paper highlight a concise and comprehensive form of land tenure system that is being applied in the Peninsular Malaysia